THE EFFECT OF STOCK RISK, PROFITABILITY AND MACROECONOMICS FACTORS ON STOCK PRICES OF BANKING COMPANIES LISTED ON IDX - Nadia Alodia; Khairina Natsir (International Journal of Application on Economics and Business, 2024)
This research aims to obtain valid evidence regarding the influence of stock risk, profitability ratios, inflation, and interest rates on share prices of banking sub-sector companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. Stock risk is proxied by beta, profitability ratio is proxied by Earning per Share (EPS), inflation is proxied by the Indonesian annual inflation rate and interest rates are measured by the BI-7 Day Reverse Repo Rate (B17DRR). This research used a descriptive research design and used quantitative data. The data in this study was extracted from official sources. The research sample was selected using purposive sampling technique. The selected research sample was 39 out of 47 banking sub sector companies listed consistently on the Indonesia Stock Exchange in the period 2018 to 2022 and produced 197 observation data. Data analysis used panel data regression which was processed using EViews 12 software. A series of tests carried out included multicollinearity tests, partial t tests and coefficient of determination tests. The research results show that earnings per share have a positive influence on share prices. Meanwhile, stock beta, inflation and interest rates have a negative influence on share prices in banking sub sector companies listed on the Indonesia Stock Exchange in the period 2018 to 2022.